NOWRUZ AND CONSUMPTION: EXAMINATION OF CONSUMPTION RITUALS OF NOWRUZCONCERNING GENERATION GROUPS - Maryam Rahmani; Mohammad Rahim Esfidani; Seyed Abolghasem Mira; Tahmoores Hasangholi Poor Yasoori (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to analyze the consumption behavior in the ritual situation of Nowruz according to the three generational groups of the 30s and 40s(50s and 60s, 70s and early 80s(according to the solar calendar).The research method is descriptive case study.The data collection method is interviews with 13 participants (8 females and 5 males) from three different generation groups who were selected using the snowball method.Then, the interview data were analyzed using the theme analysis method.The findings of this study showed that despite the changes in this ritual in recent decades, according to the criteria of survival of the ritual, it is living and dynamic andhas a variety of ritual values.Also, differences in the performance of Nowruz sub-rituals were identified among different generational groups.In addition, consumption behavior related to the collection of Nowruz rituals was analyzed.The results of this study show that the study of Nowruz as a ritual consumption situation, due to the diverse range of its sub-rituals and its impact on consumption, requires more attention by marketing and consumer behavior researchers.